Upaya Kepala Desa dalam Meningkatkan Partisipasi Masyarakat (Studi Kasus di Desa Kepanjenkidul Kecamatan Kepanjenkidul Kabupaten Blitar) - Dhiptya Ratri Anggraheni; Abdul Aziz Al Kaharudin (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to describe the village head's efforts to increase community participation in Kepanjenkidul Village, Kepanjenkidul District, Blitar Regency. Research Method: This research, based on the location of the data source, is included in the field research category, and in terms of the characteristics of the data, it is included in qualitative research, based on the discussion, it includes descriptive research using a case study approach. Data collection methods use observation, interviews and documentation. Data analysis is carried out starting from data reduction, data presentation, and drawing conclusions. Research Results: The village head's innovation in increasing community participation in development in Kepanjenkidul Village, Kepanjenkidul District, Blitar Regency is carried out by: a) always holding meetings with the community to discuss activities that need to be carried out, b) reprimanding people who are less active in participating in development activities in the village, c) Giving awards to people who are active in village development, namely giving tasks in village management, d) Firmness in leading village communities. The impact of the village head in increasing community participation in Kepanjenkidul Village, Kepanjenkidul District, Blitar Regency, namely: a) Changes in the environment to improve the standard of living of the community, so that all access is easy for the community, so that the economy can run smoothly, b) Implementation of village development will increase to provide benefits. best for the community, all access is easy for the community, so the economy can run smoothly.